"We wish we had the option": a qualitative study of women's perspectives and experiences with contraception in a provincial prison in Ontario, Canada - Reilly Jones; Sasha Lemberg-Pelly; Brigid Dineley; Jessica Jurgutis; Fiona G Kouyoumdjian; Jessica Liauw (BMC, 2024)
Abstract Background Evidence suggests that women who are incarcerated desire access to contraception while incarcerated, and that this need is not currently being met. Our objective in this study was to explore the perspectives and experiences of women in prisons regarding contraception and contraception access using data from focus groups with women in a provincial prison. We analyzed focus group data collected in a provincial prison in Ontario, Canada using content analysis and a constructivist epistemology. Results We conducted three focus groups, each approximately one hour in length. Discussions revolved around (1) knowledge and decision making about contraception, (2) accessing contraception, and (3) ideas for increasing access to contraception in the prison setting. Decision making about contraception was mainly related to concerns about side effects, consistent access to care, impacts on future fertility, and autonomy around decision-making. Participants discussed a wide range of experiences with contraception. Ideas for increasing access to contraception included information sessions, inclusion of discussions about contraception as a component of admission and release planning, and time spent in prison as a crucial juncture for decision-making about contraception. Conclusions More qualitative research is needed to better understand the needs of women in prisons related to contraception. The findings of this study suggest that programs should focus on consistency and continuity of access to care, education opportunities, and integration of discussions about contraception into official admission and release procedures.